Early Experiences With COVID-19 Testing in Transplantation. Issue 7 (July 2020) - Boyarsky, Brian J.; Massie, Allan B.; Love, Arthur D.; Werbel, William A.; Durand, Christine M.; Avery, Robin K.; Jackson, Kyle R.; Kernodle, Amber B.; Thomas, Alvin G.; Ronin, Matthew; Altrich, Michelle; Niles, Patricia; et al.
Abstract : Background: The early effects of coronavirus disease 2019 (COVID-19) on transplantation are dramatic: >75% of kidney and liver programs are either suspended or operating under major restrictions. To resume transplantation, it is important to understand the prevalence of COVID-19 among transplant recipients, donors, and healthcare workers (HCWs) and its associated mortality. Methods: To investigate this, we studied severe acute respiratory syndrome coronavirus 2 diagnostic test results among patients with end-stage renal disease or kidney transplants from the Johns Hopkins Health System (n = 235), and screening test results from deceased donors from the Southwest Transplant Alliance Organ Procurement Organization (n = 27), and donors, candidates, and HCWs from the National Kidney Registry and Viracor-Eurofins (n = 253) between February 23 and April 15, 2020. Results: We found low rates of COVID-19 among donors and HCWs (0%–1%) who were screened, higher rates of diagnostic tests among patients with end-stage renal disease or kidney transplant (17%–20%), and considerable mortality (7%–13%) among those who tested positive. Conclusions: These findings suggest the threat of COVID-19 for the transplant population is significant and ongoing data collection and reporting is critical to inform transplant practices during and after the pandemic.